Chrystianizacja Żydów bizantyńskich w drugiej połowie IX wieku: sprzeciw i aprobata - Kashchuk, Oleksandr; Melnykovych, Ruslan (Vox Patrum, 2024)
The subject of this article are several written sources created in the context of the conversion of Byzantine Jews to Christianity in the second half of the 9th century: the polemical treatise of Gregory of Nicaea (844–880) and the poems of the protoasekretis Christopher (850–900). The purpose of this article is to examine these works in terms of their standpoint towards policy of encouraging the conversion of Byzantine Jews to Christianity. The article consists of four parts: the introductory part briefly presents the information concerning the sources, the following two parts define the intended audiences for Gregory’s treatise and Christopher’s poems and the fourth part examines the intention of their works in the confrontation between supporters and opponents of the policy of Christianization of the Jews. Despite the differences in genre, the works of Christopher and Gregory were written for the purpose of propaganda and counter-propaganda for the Christianization of the Jews. The article shows the way the written texts were used by opposing sides to defend their own standpoint.